cos^2 theta (1 - cos theta) / sin^2 theta (1 - sin theta) = 1 + sin theta / 1 + cos theta
Answers
Answered by
0
Answer:
sin
2
1
∘
+sin
2
2
∘
+sin
2
2
∘
+...+sin
2
89
∘
+sin
2
90
∘
= (sin
2
1+sin
2
89)+(sin
2
+sin
2
88)+....+(sin
2
44+sin
2
46)+(sin
2
45+sin
9
0)
= (sin
2
1+cos
2
(90−1))+(sin
2
+cos
2
(90−2))+....+(sin
2
44+sin
2
(90−44))+(sin
2
45+sin
9
0)
= (sin
2
1+sin
2
1)+(sin
2
+sin
2
2)+....+(sin
2
44+cos
2
44)+(sin
2
45+sin
9
0)
= 1+1...44times+(
2
1
)
2
+1
= 45+
2
1
= 45.5
Similar questions